Uveal melanoma and its local inflammation - good or bad for the patient? - Brovkina, A F; Kabardikova, L A; Shcherbakov, P A; Bure, I V; Mirzaev, K B (Vestnik oftal'mologii, 2025)
The 21st century is characterized by the study of the features of malignant tumor infiltration by cellular components of the immune system. While some findings suggest a favorable role of lymphoid infiltration in tumors and its positive impact on survival due to immune defense, the opposite is observed in uveal melanoma (UM): lymphoid infiltration significantly worsens the patient's prognosis. Research on this topic is limited, with some studies confined to experimental models. This study investigated the correlation between microRNA-155 expression in the plasma of UM patients after primary enucleation and with pathomorphological inflammatory changes. Eighty-three patients with UM were examined, in 21 cases lymphoid infiltration of the primary tumor was detected, in 6 cases accompanied by a microenvironment. The degree of tumor infiltration with lymphocytes was estimated as a percentage of the total number of cells in the analyzed field, ranging from 1% to 25%. Real-time polymerase chain reaction was used to determine microRNA-155 expression in the plasma of all patients before and after enucleation, and its correlation with the level of lymphoid infiltration was analyzed. Postoperative follow-up lasted 6 to 53 months (mean 21.5±14.9 months). In two cases, in the presence of a tumor microenvironment, metastases to the liver were detected 6 and 10 months after enucleation. MicroRNA-155 levels in a volunteer group were used as the control baseline, set at 100% for clarity and convenience. MicroRNA-155 expression levels were higher in patients with lymphoid infiltration ( <0.05) and tended to increase with the degree of primary tumor infiltration ( <0.001), which in itself, with the appearance of a perifocal lymphoid environment, indicated a poor prognosis. Monitoring microRNA-155 expression levels in the plasma of UM patients may help predict occult metastasis prior to enucleation. This is not only crucial for clinical follow-up but may also play a significant role in the development of targeted therapies.